The Changes in Some Hematological Parameters among University Students Due to Stressful Conditions During and after Examinations Period - Jehad F. Alhmoud1 , Husni S. Farah2 , Talal Al-Qaisi1 , Wala, a Hamdan3 , Ghaleb A. Oriquat4 , Ali A (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Several studies demonstrated that stress can cause an obvious change in the hematologicalparameters in healthy individuals. In the current study, we determined whether the stress during the examscan produce some hematological changes and how long this effect may take after the end of the exam period.Methods: Seventy (n= 70) male and sixty (n=60) female student of similar height, weight and age wereselected from the department of medical laboratory sciences, Al-Ahliyya Amman university. All studentswere first had a preliminary medical checkup. Students excluded from the study include those who had achronic disease and any health issues or habits affecting the studied parameters, such as smoking; feverand high blood pressure. All study participants were between the age group of 20-22 years. Blood sampleswere taken three weeks before the exam, during and 72 hours after the end of the exam period. Estimationsof red blood cells (RBC), white blood cells (WBC), hematocrit, mean corpuscular volume (MCV), meancorpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), neutrophils,lymphocytes and platelets were accomplished.Results: Compared with pre-examination results the blood samples taken during exams showed a significantdecrease in the readings of lymphocytes (p <0.01) , MCV and MCH (p < 0.05). Significant increase inNeutrophil (p < 0.05) and platelets (p< 0.05). Readings taken after 72 hours of the end of exam periodshowed significant decrease in white blood cell count (p < 0.01) and further significant increase in theplatelet count (p <0.001). No significant changes were observed in the readings of Hemoglobin, Red BloodCell count (RBC), hematocrit and mean corpuscular hemoglobin concentration (p >0.2).Conclusion: This study concluded that the stress due to examinations is enough to alter certain hematologicalparameters. The effect of stress on platelets and WBC remained until the end of the exam period. As theincreased platelet count may cause health problems for a person, from bleeding problems to the formationof various clots. We do not know for sure how long the increase in platelet and decrease in white blood cellscontinue as this may cause health problems for people subject to permanent stress.